Ganoderma lucidum spore extract improves sleep disturbances in a rat model of sporadic Alzheimer’s disease - Qin, Yu; Zhao, Yan; Hu, Xiao; Chen, Xi; Jiang, Yan-Ping; Jin, Xue-Jun; Li, Gao; Li, Zhen-Hao; Yang, Ji-Hong; Zhang, Guo-Liang; Cui, Su-Ying; Zhang, Yong-He (Frontiers in Pharmacology, 2024)
Ganoderma lucidum (G. lucidum, Lingzhi) has long been listed as a premium tonic that can be used to improve restlessness, insomnia, and forgetfulness. We previously reported that a rat model of sporadic Alzheimer's disease (sAD) that was induced by an intracerebroventricular injection of streptozotocin (ICV-STZ) showed significant learning and cognitive deficits and sleep disturbances. Treatment with a G. lucidum spore extract with the sporoderm removed (RGLS) prevented learning and memory impairments in sAD model rats. The present study was conducted to further elucidate the preventive action of RGLS on sleep disturbances in sAD rats. The results showed that treatment with 720 mg/kg RGLS for 14 days significantly improved the reduction of total sleep time, rapid eye movement (REM) sleep time, and non-REM sleep time in sAD rats. The novelty recognition experiment further confirmed that RGLS prevented cognitive impairments in sAD rats. We also found that RGLS inhibited the nuclear factor-κB (NF-κB)/Nod-like receptor family pyrin domain-containing 3 (NLRP3) inflammatory pathway in the medial prefrontal cortex (mPFC) in sAD rats and ameliorated the lower activity of γ-aminobutyric acid (GABA)-ergic neurons in the parabrachial nucleus (PBN). These results suggest that inhibiting the neuroinflammatory response in the mPFC may be a mechanism by which RGLS improves cognitive impairment. Additionally, improvements in PBN-GABAergic activity and the suppression of neuroinflammation in the mPFC in sAD rats might be a critical pathway to explain the preventive effects of RGLS on sleep disturbances in sAD.